Taking the lead for campus-community-partnerships in Austria - Fahrenwald, Claudia; Resch, Katharina; Rameder, Paul; Fellner, Magdalena; Slepcevic-Zach, Peter; Knapp, Mariella (Frontiers in Education, 2023)
Higher Education Institutions (HEIs) have been going through far-reaching processes of transformation in terms of their missions in teaching, research, and societal impact. Contrary to their previous understanding and mission, Austrian universities are now increasingly required to contribute evidence from research and teaching to meet social challenges and to cooperate with community partners. This forces an understanding of HEIs as a driver for social innovation and requires educational leadership on multiple levels (Fassi et al., 2020). Overall, campus community partnerships (CCPs) emerge as a dimension of a new culture of cooperation between HEIs and civil society (Zeichner, 2010; Felten & Clayton, 2011). Against this background, the questions arise (1) to which degree these partnerships have been institutionalized and supported so far and (2) who takes the lead for their initiation and maintenance. These questions are discussed in the framework of their significance for educational leadership for the establishment of suitable framework conditions for the promotion of social innovation for CCPs. These questions are particularly of interest for Austria, since CCPs in the context of teaching still have little tradition across the higher education sector. This requires both a national and comparative approach to analyzing the state-of-the art of CCPs in the four different types of higher education institutions in Austria. In this context, the article outlines the educational policy framework of the current HEI development discourse in Austria (Resch et al., 2020), and then draws conclusions for educational leadership principles for CCPs, for Austria and beyond.